Audience Perceptions of News Media Trustworthiness in the Digital Age - Hussain, Sadam; Adnan, Malik; Sohail, Rana Babar (Annals of Human and Social Sciences, 2024)
This study aims to investigate the evolving landscape of audience perceptions regarding the trustworthiness of news media in the digital age. As technology continues to shape the way information is disseminated, consumed, and shared, it becomes crucial to explore the factors influencing public trust in news sources. Through a comprehensive analysis of user attitudes, consumption patterns, and the impact of digital platforms, this research seeks to provide valuable insights into how news media can adapt and enhance their credibility in an era marked by rapid technological advancements and information abundance. In the contemporary Digital Age, where information dissemination is profoundly influenced by technological advancements, this study seeks to investigate the evolving perceptions of audience trust in news media. As the digital landscape continues to reshape the way information is consumed and shared, it becomes imperative to comprehend the intricate factors that impact public trust in news sources. Traditional news media outlets are encountering challenges to their credibility due to the accessibility and abundance of information facilitated by digital platforms. The background of this study underscores the necessity of exploring audience attitudes and understanding how changes in media consumption patterns correlate with shifts in perceptions of news media trustworthiness. Employing a comprehensive methodology, the study integrates surveys, content analysis, and user behavior studies. By collecting data on audience attitudes, information sources, and technology usage, the research aims to unveil the intricate dynamics that influence trust in news outlets in the contemporary digital environment. This study Emphasizes strategies for transparent communication, technological integration, and adaptation to evolving audience expectations.